"We feel that our strength is on the factory floor": Dualism, shop-floor power, and labor law reform in late apartheid South Africa. (2nd November 2019) - Lichtenstein, Alex
ABSTRACT: This article explores the transformation of South African labor relations during the 1980s. In 1979, prompted by new shop-floor militancy, the Wiehahn Commission recommended that black workers, previously excluded from state labor machinery, be permitted to join recognized trade unions. Most discussions of this shift in apartheid labor relations focus on the ensuing debate within the black unions, torn between preserving their independence or securing state legitimation. This article looks instead at the related debate about 'levels of bargaining': should emergent black unions demand to negotiate at the factory level, where they had secured shop-floor strength through organizing and democratic practice, or pursue the benefits of the corporatist bargaining structures that had long excluded them and had privileged white workers? The eventual drift towards corporatism, I argue, imprinted the character of the South African labor movement into the post-apartheid era. An understandable desire to wield influence at the level of the national political economy eroded the tradition of workers' control, shop floor democracy, and struggle unionism that black unions had forged during the 1970s and 1980s.